Five‐year incidence and progression of myopic maculopathy in a rural Chinese adult population: the Handan Eye Study. (24th April 2018) - Lin, Caixia; Li, Shi‐Ming; Ohno‐Matsui, Kyoko; Wang, Bing Song; Fang, Yu Xin; Cao, Kai; Gao, Li Qin; Hao, Jie; Zhang, Ye; Wu, Jian; Wang, Ning Li
Abstract: Purpose: To determine the cumulative five‐year incidence and progression of myopic maculopathy in a rural Chinese adult population. Methods: The Handan Eye Study was a population‐based longitudinal study. In 2006, 6830 subjects aged 30+ years participated in this study (baseline). Five years later, 5394 subjects (follow‐up rate: 85.3%) took part in the follow‐up study. Participants had a detailed eye examination, including visual acuity, standardized refraction and fundus photography according to a similar protocol at both baseline and follow‐up. Myopic maculopathy was defined as any of the following signs: diffuse chorioretinal atrophy, patchy chorioretinal atrophy, macular atrophy, lacquer cracks and myopic choroidal neovascularization at the posterior pole. Parapapillary atrophy was assessed separately. Results: Of 5394 participants, 5078 (10 021 eyes) had gradable fundus photographs. Over the five years, four participants (five eyes) developed new myopic maculopathy, with an eye‐specific incidence of 0.05% (95% CI, 0.02–0.10%). Among the 51 eyes with myopic maculopathy at baseline, the progression occurred in 18 eyes (35.3%), with new signs of patchy chorioretinal atrophy in 11 eyes (21.6%), diffuse chorioretinal atrophy in seven eyes (13.7%), lacquer cracks in three eyes (6.9%), macular atrophy in three eyes (6.9%) and myopic choroidal neovascularization in two eyes (3.9%). By multivariable analysis, female gender (OR, 9.14; p  =   0.004) and higher educational level (OR, 8.24; p  =   0.004) were associated with a higher risk of progression of myopic maculopathy, whereas lower myopia at baseline (OR, 0.79; p  <   0.0001) and hypertension (OR, 0.21; p  =   0.017) were associated with a reduced risk. Conclusions: The five‐year incidence of myopic maculopathy was 0.05% in rural Chinese adults aged 30+ years. The progression rate in participants with myopic maculopathy was 35.3%, indicating the importance of regular follow‐up for these patients.